2019
DOI: 10.1016/bs.apcsb.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor signaling mechanisms

Abstract: The primary female sex hormones, estrogens, are responsible for the control of functions of the female reproductive system, as well as the development of secondary sexual characteristics that appear during puberty and sexual maturity. Estrogens exert their actions by binding to specific receptors, the estrogen receptors (ERs), which in turn activate transcriptional processes and/or signaling events that result in the control of gene expression. These actions can be mediated by direct binding of estrogen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
580
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(593 citation statements)
references
References 179 publications
2
580
0
11
Order By: Relevance
“…Asthma is characterized by inflammation and remodeling in the airways contributing to airway hyperresponsiveness (AHR) leading to episodic bronchoconstriction's (Holgate et al, 2009;Prakash, 2013;Prakash and Martin, 2014;Sathish et al, 2015b;Prakash, 2016). Epidemiological data suggests a role of sex in a variety of lung diseases, especially asthma (Riffo-Vasquez et al, 2007;Antunes et al, 2010;Bonds and Midoro-Horiuti, 2013;Lingappan et al, 2016;Wang et al, 2016;DeBoer et al, 2018;Fuentes and Silveyra, 2019a;Naeem and Silveyra, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma is characterized by inflammation and remodeling in the airways contributing to airway hyperresponsiveness (AHR) leading to episodic bronchoconstriction's (Holgate et al, 2009;Prakash, 2013;Prakash and Martin, 2014;Sathish et al, 2015b;Prakash, 2016). Epidemiological data suggests a role of sex in a variety of lung diseases, especially asthma (Riffo-Vasquez et al, 2007;Antunes et al, 2010;Bonds and Midoro-Horiuti, 2013;Lingappan et al, 2016;Wang et al, 2016;DeBoer et al, 2018;Fuentes and Silveyra, 2019a;Naeem and Silveyra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of asthma is more common in pre-pubescent boys and adult women and the severity of asthma is increased during pregnancy (de Marco et al, 2000;Caracta, 2003;Carey et al, 2007b;Bonds and Midoro-Horiuti, 2013). In this context, multiple studies have explored and suggested a role for sex hormones in airway biology, especially estrogen (Keselman and Heller, 2015;Sathish et al, 2015a;Ambhore et al, 2018;Ambhore et al, 2019a;Ambhore et al, 2019b;Bhallamudi et al, 2019;Fuentes et al, 2019;Fuentes and Silveyra, 2019a). However, there is still a debate on the contradicting role of estrogen as few studies suggest its role in reducing inflammation (Myers and Sherman, 1994;Lieberman et al, 1995;Haggerty et al, 2003), while others suggest estrogen to induce AHR and inflammation (Riffo-Vasquez et al, 2007;Sakazaki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 70% of human breast cancers are hormone-dependent and estrogen receptor (ER)-positive (168). In mammals there are two ERs, ER (595 amino acids; 67 kDa) and ER (530 amino acids; 59 kDa), both members of the nuclear receptor superfamily of hormone-inducible transcription factors (169,170). Although most ERs localize in tumor cell nuclei, where they are translocated as dimers to induce transcriptional changes in estrogen-responsive genes, a significant pool of ERs occurs in extranuclear sites in tumor cells (171).…”
Section: Estrogen Receptormentioning
confidence: 99%
“…Many studies have confirmed that estrogen is involved in the development of human breast cancer (1,2). Since estrogen needs to bind to its receptors to function, an in-depth understanding of its two receptors, estrogen receptor α (ER α) and ER β, is essential to explore the pathogenesis of breast cancer (3). Currently, the medical community has a thorough understanding of the role of ER α in the development of breast cancer and uses this knowledge to guide the endocrine treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%